Carbon material dispersion and use thereof

The carbon material dispersion with specific dispersant and binder resin ratios addresses the challenge of achieving high conductivity and flexibility in thin films, resulting in stable and uniform coatings for diverse applications.

JP7620126B1Active Publication Date: 2025-01-22DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024007392
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-22
Publication Date
2025-01-22
Estimated Expiration
2044-01-22

AI Technical Summary

Technical Problem

Existing carbon material dispersions struggle to achieve high conductivity and good physical properties in thin films at low concentrations, leading to difficulties in forming uniform and durable coatings with both high conductivity and flexibility.

Method used

A carbon material dispersion containing single-walled or multi-walled carbon nanotubes, an aqueous medium, a dispersant, and a binder resin, with specific ratios of dispersant and binder resin to carbon nanotubes, and a defined surface resistivity and absorbance ratio, ensuring uniform dispersion and high conductivity.

Benefits of technology

The solution enables the formation of a coating film with high conductivity and good physical properties in a thin film state at low carbon material concentration, providing stable and uniform coatings suitable for various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620126000001
    Figure 0007620126000001
  • Figure 0007620126000002
    Figure 0007620126000002
  • Figure 0007620126000003
    Figure 0007620126000003
Patent Text Reader

Abstract

The present invention provides a carbon material dispersion capable of forming a coating film having improved conductivity in a thin film state at a low concentration of a conductive material. [Solution] A carbon material dispersion contains at least one type of carbon material selected from single-walled carbon nanotubes and multi-walled carbon nanotubes, an aqueous medium, a dispersant, and a binder resin, and satisfies the following requirements (1), (2), and (3). (1) The amounts of dispersant and binder resin relative to the carbon material are within predetermined ranges for each type of carbon material. (2) The surface resistivity of a dry film with a thickness of 1 μm and a carbon material content of 10 mass% is 1.0 × 10 3 It is less than Ω / sq. (3) The absorbance A at 780 nm of the diluted dispersion obtained by diluting with a blank solution so that the absorbance at 580 nm is 1.8 ± 0.02. H Absorbance A at a wavelength of 380 nm L Ratio of (A L / A H ) is 1.45 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbon material dispersion and uses thereof. [Background technology]

[0002] Carbon materials (nanocarbon materials) such as carbon black, carbon fiber, carbon nanotubes (hereinafter also referred to as "CNT"), graphite, and graphene have a six-membered ring graphite structure formed by covalent bonds of carbon atoms. For this reason, they are materials that exhibit various properties such as electrical conductivity and thermal conductivity, and methods for utilizing these properties in a wide range of fields are being considered. For example, focusing on the electrical properties, thermal properties, and properties as a filler of carbon materials, their use as antistatic agents, conductive materials, plastic reinforcing materials, semiconductors, electrodes for fuel cells or secondary batteries, and cathode rays for displays is being considered.

[0003] In recent years, these applications have required higher performance, and CNTs have been widely used as carbon materials. In order to improve various physical properties such as electrical conductivity, the type and amount of dispersant for dispersing CNTs in a liquid medium, as well as the selection of binder resins used when forming coatings or electrodes, are also important.

[0004] As related prior art, for example, there has been proposed an aqueous CNT dispersion that is a dispersion containing CNTs with an average outer diameter of 3 nm or less and a dispersant, and is characterized in that the average particle size measured by dynamic light scattering is 200 nm or more and 1500 nm or less, as well as a method of evaluating the electrical conductivity of CNTs by measuring the surface resistance of a coating film obtained by drying the dispersion (Patent Document 1).

[0005] In addition, a method has been proposed for evaluating the electrical conductivity of CNTs by measuring the surface resistance of a resin composition containing CNTs and a resin synthesized using a specific catalyst, as well as a coating film containing the synthesized CNTs (Patent Document 2).

[0006] In addition, the antistatic layer is formed by a binder resin and single-walled carbon nanotube paint, and the surface resistivity is 3.0 × 10 5 An antistatic sheet with a resistance of Ω / sq or less has been proposed (Patent Document 3). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2010-254546 A [Patent Document 2] JP 2015-123410 A [Patent Document 3] Patent Publication No. 2021-195546 Summary of the Invention [Problem to be solved by the invention]

[0008] In general, the thicker the conductive paint coating layer is, the higher the conductivity is. For example, if the coating layer is made very thin, 1 μm thick, to reduce the size and weight of the conductive paint coating, the conductive conductivity is only 1.0 × 10 3 It was difficult to obtain a high conductivity of less than Ω / sq.

[0009] Increasing the concentration of the conductive material in the coating generally improves the conductivity. However, the concentration of the binder resin in the coating is relatively decreased, so that the properties of the binder resin, such as elongation or bending, are not easily reflected, making it difficult to obtain a uniform coating. Even if a uniform coating is obtained, the durability of the coating, such as flexibility and adhesion, is reduced, making it difficult to achieve both high conductivity and good coating film properties.

[0010] A carbon material dispersion containing CNTs is used, for example, as a material for improving the electrical conductivity of a target article, etc. The electrical conductivity of the carbon material dispersion can be evaluated, for example, by measuring the surface resistivity of a coating film formed by applying and drying the carbon material dispersion.

[0011] The present inventors formed coating films using the conventional CNT dispersions proposed in Patent Documents 1 and 2, and evaluated the electrical conductivity of the formed coating films by measuring the surface resistivity of the coating films. As a result, it was found that none of the coating films formed using the CNT dispersions etc. exhibited the high level of electrical conductivity required in recent years at a thin film and low concentration.

[0012] Furthermore, in Patent Document 3, the thickness of the antistatic layer is set to 1 μm or less, and the amount of carbon nanotubes added is kept as low as possible, thereby achieving a surface resistivity of 3.0 × 10 5 Antistatic sheets have been proposed that have a surface resistivity of 1.0×10 3 No study has been done to achieve both high electrical conductivity of Ω / sq or less and good coating film properties.

[0013] The present invention has been made in consideration of the problems of the prior art, and an object of the present invention is to provide a carbon material dispersion capable of forming a coating film having improved conductivity in a thin film state and at a low concentration of conductive material. Another object of the present invention is to provide a use of the carbon material dispersion for producing various products and films that are components of various products. [Means for solving the problem]

[0014] That is, according to the present invention, there is provided the following carbon material dispersion. [1] A carbon material comprising at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes, an aqueous medium, a dispersant, and a binder resin; A carbon material dispersion that satisfies the following requirements (1), (2), and (3): (1) when the carbon material contains the single-walled carbon nanotubes, the amount of the dispersant relative to 100 parts by mass of the single-walled carbon nanotubes is 50 parts by mass or more and 600 parts by mass or less, and the amount of the binder resin relative to 100 parts by mass of the single-walled carbon nanotubes is 300 parts by mass or more and 850 parts by mass or less, When the carbon material contains the multi-walled carbon nanotubes, the amount of the dispersant per 100 parts by mass of the multi-walled carbon nanotubes is 20 parts by mass or more and 200 parts by mass or less, and the amount of the binder resin per 100 parts by mass of the multi-walled carbon nanotubes is 700 parts by mass or more and 880 parts by mass or less. (2) The surface resistivity of a dry film having a thickness of 1 μm and containing 10% by mass of the carbon material is 1.0 × 10 3 It is less than Ω / sq. (3) The absorbance A at a wavelength of 780 nm of a dilute dispersion obtained by diluting the carbon material dispersion with a blank liquid having the same composition as the carbon material dispersion except that it does not contain the carbon material so that the absorbance at a wavelength of 580 nm is 1.8 ± 0.02. H Absorbance A at a wavelength of 380 nm L Ratio of (A L / A H ) is 1.45 or greater. [2] The dispersant is at least one of a polymer dispersant and a cellulose derivative; The carbon material dispersion according to [1], wherein the polymer dispersant is a styrene-maleic acid modified polymer or a polymer having a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid. [3] The carbon material dispersion liquid according to [1], wherein the binder resin is at least one selected from the group consisting of cellulose derivatives, styrene-butadiene copolymers, and acrylic resins. [4] The average length of the single-walled carbon nanotubes is 5 μm or more and 600 μm or less; The carbon material dispersion according to [1], wherein the multi-walled carbon nanotubes have an average length of 30 μm or more and 5,000 μm or less. [5] The carbon material dispersion according to [1], wherein a concentration of the carbon material in the carbon material dispersion is 20 mass % or less. [6] Use of the carbon material dispersion according to any one of [1] to [5] for producing any one of products including paints, inks, coating agents, resin molding materials, conductive materials, thermally conductive materials, and antistatic materials. [7] Use of the carbon material dispersion according to any one of [1] to [5] for producing any one of a battery material and a mechanical part, the product having a coating formed from the carbon material dispersion. Effect of the Invention

[0015] According to the present invention, it is possible to provide a carbon material dispersion capable of forming a coating film having both high electrical conductivity and good coating film properties in a thin film state and at a low carbon material concentration. Also, according to the present invention, it is possible to provide use of the carbon material dispersion for producing various products and films that are to be components of various products. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Carbon material dispersion> Hereinafter, an embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. One embodiment of the carbon material dispersion of the present invention contains at least one carbon material selected from single-walled carbon nanotubes and multi-walled carbon nanotubes, an aqueous medium, a dispersant, and a binder resin. The carbon material dispersion according to this embodiment satisfies the following requirements (1), (2), and (3). Hereinafter, the carbon material dispersion of the present invention (hereinafter also simply referred to as "dispersion") will be described in detail.

[0017] (1) when the carbon material contains the single-walled carbon nanotubes, the amount of the dispersant relative to 100 parts by mass of the single-walled carbon nanotubes is 50 parts by mass or more and 600 parts by mass or less, and the amount of the binder resin relative to 100 parts by mass of the single-walled carbon nanotubes is 300 parts by mass or more and 850 parts by mass or less, When the carbon material contains the multi-walled carbon nanotubes, the amount of the dispersant per 100 parts by mass of the multi-walled carbon nanotubes is 20 parts by mass or more and 200 parts by mass or less, and the amount of the binder resin per 100 parts by mass of the multi-walled carbon nanotubes is 700 parts by mass or more and 880 parts by mass or less. (2) The surface resistivity of a dry film having a thickness of 1 μm and containing 10% by mass of the carbon material is 1.0 × 10 3 It is less than Ω / sq. (3) The absorbance A at a wavelength of 780 nm of a dilute dispersion obtained by diluting the carbon material dispersion with a blank liquid having the same composition as the carbon material dispersion except that it does not contain the carbon material so that the absorbance at a wavelength of 580 nm is 1.8 ± 0.02. H Absorbance A at a wavelength of 380 nm L Ratio of (A L / A H ) is 1.45 or greater.

[0018] (Carbon materials) The carbon material includes at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes. The carbon nanotubes may be doped with a metal or a metal salt such as platinum or palladium. The carbon nanotubes may be surface-modified by oxidation treatment, plasma treatment, radiation treatment, corona treatment, coupling treatment, or the like.

[0019] The average length of the single-walled carbon nanotubes (hereinafter also referred to as "SWCNTs") is preferably 5 μm or more and 600 μm or less, more preferably 10 μm or more and 500 μm or less. The average length of the multi-walled carbon nanotubes (hereinafter also referred to as "MWCNTs") is preferably 30 μm or more and 5,000 μm or less. When the dispersion according to this embodiment is used as a constituent material of a battery, it is preferable that the average length of the MWCNTs is 50 μm or more and 3,000 μm or less, since the surface resistivity of the coating film formed can be further reduced.

[0020] The dispersion according to the present embodiment may further contain other carbon materials in addition to the above carbon materials. Examples of the other carbon materials that can be used include carbon black, carbon fiber, graphite, and graphene.

[0021] Examples of carbon black (hereinafter also referred to as "CB") include acetylene black, furnace black, thermal black, and Ketjen black. The average primary particle size of CB is preferably 10 nm or more and 60 nm or less. The carbon material may be doped with a metal or a metal salt such as platinum or palladium. The carbon material may also be surface-modified by oxidation treatment, plasma treatment, radiation treatment, corona treatment, coupling treatment, or the like.

[0022] Examples of carbon fibers include PAN-based carbon fibers made from polyacrylonitrile, pitch-based carbon fibers made from pitches, and recycled products thereof. Among these, carbon nanofibers having a nano-sized fiber diameter and a cylindrical shape formed by rolling up a hexagonal graphite ring structure are preferred. Graphite is a layered material containing hexagonal plate-like crystals made of carbon. Among these, graphene, which is a single layer of graphite peeled off to a thickness of one atom, or graphene formed from multiple layers can be used.

[0023] The other carbon materials may be doped with a metal or a metal salt such as platinum or palladium, etc. Furthermore, the other carbon materials may be surface-modified by oxidation treatment, plasma treatment, radiation treatment, corona treatment, coupling treatment, etc.

[0024] The average length of CNTs and the average primary particle size of carbon black can be measured using a dispersing device such as an ultrasonic homogenizer to disperse CNTs in a solvent such as water, and then using a light scattering method with a dynamic light scattering particle size distribution measuring device, or by calculation from SEM images of CNT powder.

[0025] The CNT content in the CNT dispersion is preferably 30% by mass or less, and more preferably 20% by mass or less.

[0026] (aqueous medium) The carbon material dispersion according to this embodiment contains an aqueous medium that serves as a liquid medium to disperse the carbon material in. That is, the dispersion according to this embodiment is an aqueous dispersion of a carbon material.

[0027] As the aqueous medium, water or a mixed solvent of water and a water-soluble organic solvent can be used. Examples of the water-soluble organic solvent include alcohols such as methanol, ethanol, and isopropyl alcohol; polyhydric alcohols such as ethylene glycol, propylene glycol, and glycerin; ethers such as tetrahydrofuran; glycol ethers such as diethylene glycol, triethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol monomethyl ether, and tripropylene glycol monomethyl ether; glycol ether esters such as diethylene glycol monomethyl ether acetate; amides such as pyrrolidone, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, and 3-butoxy-N,N-dimethylpropanamide; urea-based solvents such as tetramethylurea and dimethyl-1,3-imidazolidinone; sulfur-containing solvents such as dimethyl sulfoxide and sulfolane; and ionic liquids such as 1-ethyl-3-methylimidazolium chloride. Of these, alcohols and N-methylpyrrolidone (NMP) are preferred.

[0028] The content of the water-soluble organic solvent in the carbon material dispersion is preferably 70% by mass or less, and more preferably 50% by mass or less.

[0029] (Dispersant) The dispersant is a component for dispersing the carbon material in a liquid medium. Examples of the dispersant include anionic, cationic, nonionic, and amphoteric surfactants; polymer dispersants; and cellulose derivatives. Among these, it is preferable to use at least one of the polymer dispersants and the cellulose derivatives as the dispersant.

[0030] Examples of cellulose derivatives include methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and metal salts thereof. Among these, carboxymethyl cellulose and carboxymethyl cellulose sodium salt are preferred. Furthermore, it is preferred that the cellulose derivative has a viscosity of 20 mPa·s or more and 500 mPa·s or less in a 1% by mass aqueous solution and a degree of etherification of 0.5 or more and 0.9 or less. By using such a cellulose derivative, the carbon material can be better dispersed and storage stability can be improved.

[0031] The polymer dispersant is preferably a styrene-maleic acid modified polymer or a polymer having a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid, and is preferably a polymer substantially composed of only the structural unit (1) derived from (meth)acrylonitrile and the structural unit (2) derived from (meth)acrylic acid. The polymer dispersant is also preferably a polymer having a carboxyl group at least a part of which is neutralized with an alkali.

[0032] Examples of styrene-maleic acid modified polymers include commercially available dispersants such as "Floren GW-1500" (manufactured by Kyoeisha Chemical Co., Ltd., polyalkylene glycol modified styrene-maleic acid copolymer, having a carboxyl group as a functional group directly bonded to the polymer chain, acid value 55 mg KOH / g, amine value 0 mg KOH / g, weight average molecular weight 5,000), "DISPERBYK-190" (manufactured by BYK-Chemie, polyalkylene glycol modified styrene-maleic acid copolymer, acid value 10 mg KOH / g, amine value 0 mg KOH / g), and "TEGO Dispers 755W" (manufactured by Evonik, polyalkylene glycol modified styrene-maleic acid copolymer, acid value 10 mg KOH / g, amine value 0 mg KOH / g).

[0033] The structural unit (1) has a cyano group (-CN) derived from (meth)acrylonitrile. Therefore, the triple bond of the cyano group acts on the surface of the carbon material, and the polymer serving as a dispersant is electronically adsorbed to the carbon material. In addition, the structural unit (2) has a carboxy group derived from (meth)acrylic acid. Therefore, by neutralizing and ionizing at least a portion of this carboxy group with an alkali, the polymer serving as a dispersant can be dissolved in an aqueous medium. By using a polymer containing these structural units (1) and (2) as a dispersant, it is possible to finely disperse the carbon material in an aqueous medium for a long period of time.

[0034] The proportion of the structural unit (1) derived from (meth)acrylonitrile in the polymer is 50% by mass or more and 80% by mass or less, preferably 55% by mass or more and 75% by mass or less. The proportion of the structural unit (2) derived from (meth)acrylic acid in the polymer is 20% by mass or more and 50% by mass or less, preferably 25% by mass or more and 45% by mass or less. The sum of the structural unit (1) and the structural unit (2) is 100% by mass. If the proportion of the structural unit (2) in the polymer is less than 20% by mass, the water solubility of the polymer tends to be insufficient. On the other hand, if the proportion of the structural unit (2) in the polymer is more than 50% by mass, the water solubility of the polymer tends to be excessively high. For this reason, the viscosity of the carbon material dispersion becomes excessively high, and the amount of hydrophilic carboxyl groups is large, so that the water resistance of the coating film formed may decrease.

[0035] The polymer dispersant (polymer) may further have other structural units other than the structural unit (1) and the structural unit (2). Examples of monomers constituting the other structural units include conventionally known styrene-based monomers and (meth)acrylate-based monomers. In particular, it is preferable to use monomers that do not contain structures that are easily hydrolyzed, such as ester bonds and amide bonds. Examples of such monomers include styrene, vinyl naphthalene, vinyl toluene, vinyl biphenyl, and vinyl alcohol.

[0036] The polymer used as the polymer dispersant may be either a random copolymer or a block copolymer. However, in the case of a random copolymer, the hydrophilic and hydrophobic groups are randomly present, so that the effect as a dispersant may be somewhat reduced. In addition, when a binder resin having high hydrophilicity is further used, the influence of the binder resin may be more significant. For this reason, the polymer used as the polymer dispersant is preferably a block copolymer.

[0037] The polymer that is the polymer dispersant is preferably an AB block copolymer including a polymer block A having a structural unit (1-A) derived from acrylonitrile and a structural unit (2-A) derived from methacrylic acid, and a polymer block B having a structural unit (1-B) derived from acrylonitrile and a structural unit (2-B) derived from methacrylic acid. The polymer block A is preferably a polymer block substantially composed only of the structural unit (1-A) derived from acrylonitrile and the structural unit (2-A) derived from methacrylic acid. The polymer block B is preferably a polymer block substantially composed only of the structural unit (1-B) derived from acrylonitrile and the structural unit (2-B) derived from methacrylic acid.

[0038] The proportion of the structural unit (1-A) derived from acrylonitrile in the polymer block A (hereinafter also referred to as "A chain") is preferably 60% by mass or more and 95% by mass or less, more preferably 65% ​​by mass or more and 90% by mass or less. The proportion of the structural unit (2-A) derived from methacrylic acid in the A chain is preferably 5% by mass or more and 40% by mass or less, more preferably 10% by mass or more and 35% by mass or less. The total of the structural unit (1-A) and the structural unit (2-A) is taken as 100% by mass.

[0039] The A chain is a polymer block having a lower content of carboxy groups than the polymer block B (hereinafter also referred to as the "B chain") and a relatively low water solubility. Therefore, the A chain adsorbed to the carbon material is less likely to be detached than the B chain, and has the function of further improving the dispersibility of the carbon material. If the proportion of the structural unit (2-A) in the A chain is less than 5% by mass, the water solubility of the A chain may be insufficient. On the other hand, if the proportion of the structural unit (2-A) in the A chain is more than 40% by mass, the water solubility of the A chain may be too high, and the A chain may be more likely to be detached from the carbon material.

[0040] The number average molecular weight of the polymer block A (A chain) is preferably 10,000 or more and 100,000 or less, more preferably 20,000 or more and 90,000 or less. If the number average molecular weight of the A chain is less than 10,000, the adsorption to the carbon material tends to be insufficient. On the other hand, if the number average molecular weight of the A chain is more than 100,000, the water solubility may be insufficient even if the polymer has a structural unit (2-A) having a carboxy group.

[0041] The molecular weight distribution (PDI=weight average molecular weight (Mw) / number average molecular weight (Mn)) of the polymer block A (A chain) is preferably 1.8 or less, more preferably 1.6 or less. A relatively uniform molecular weight allows for more uniform adsorption to the carbon material and further improves dispersibility. If the molecular weight distribution (PDI value) of the A chain exceeds 1.8, many polymer blocks outside the above-mentioned number average molecular weight range will be contained, which may reduce the effect of improving dispersibility.

[0042] The proportion of the structural unit (1-B) derived from acrylonitrile in the polymer block B (B chain) is preferably 10% by mass or more and 70% by mass or less, more preferably 15% by mass or more and 65% by mass or less. The proportion of the structural unit (2-B) derived from methacrylic acid in the B chain is preferably 30% by mass or more and 90% by mass or less, more preferably 35% by mass or more and 85% by mass or less. The total of the structural unit (1-B) and the structural unit (2-B) is taken as 100% by mass. The number average molecular weight of the B chain is preferably 3,000 or more and 200,000 or less, more preferably 5,000 or more and 60,000 or less. If the number average molecular weight of the B chain is less than 3,000, it tends to be difficult to dissolve in water. On the other hand, if the number average molecular weight of the B chain is more than 200,000, the viscosity tends to increase excessively, making it difficult to disperse.

[0043] The B chain is a polymer block that contains more carboxy groups than the A chain and has relatively high water solubility. If the proportion of the structural unit (2-B) in the B chain is less than 30% by mass, the water solubility of the entire AB block copolymer may be insufficient. On the other hand, if the proportion of the structural unit (2-B) in the B chain is more than 90% by mass, the water affinity may be excessively high. As a result, the viscosity of the carbon material dispersion may become excessively high and the water resistance of the formed coating film may decrease.

[0044] The AB block copolymer can be produced, for example, by a living radical polymerization method. Since the AB block copolymer is composed of acrylonitrile and methacrylic acid, it is easy to control the structure and adjust the molecular weight.

[0045] Examples of the alkali that neutralizes at least a portion of the carboxy groups in the polymer dispersant (polymer) include conventionally known alkalis such as ammonia, organic amines such as triethylamine and dimethylaminoethanol, and alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide. Among these, from the viewpoints of improving water solubility and improving the electrical conductivity of the coating film by ionic action, it is preferable that the alkali is at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide.

[0046] All the carboxy groups in the polymer may be neutralized with an alkali, but it is also preferable to neutralize only some of the carboxy groups with an alkali as long as the polymer is soluble in water. The carboxy groups (-COOH) that are not neutralized with an alkali can form hydrogen bonds with the carbon material. Therefore, by using a polymer in which only some of the carboxy groups are neutralized with an alkali as a dispersant, the dispersion stability of the carbon material dispersion can be further improved. The amount of alkali used to neutralize the carboxy groups is preferably an amount equivalent to 50 mol % to 120 mol % of the carboxy groups, and more preferably an amount equivalent to 70 mol % to 110 mol % of the carboxy groups.

[0047] The polymer used as the polymer dispersant can be produced according to a conventionally known method. In particular, it can be produced by a solution polymerization method using an organic solvent; and a radical polymerization method using an azo-based radical generator or a peroxide-based radical generator. As the organic solvent, a conventionally known organic solvent can be used. However, since the polymer may be difficult to dissolve in a general-purpose organic solvent, it is preferable to use a polar organic solvent that can be dissolved in water. Examples of such polar organic solvents include amide-based solvents, sulfoxide-based solvents, urea-based solvents, and nitrile-based solvents. In particular, it is preferable to use amide-based solvents, urea-based solvents, and nitrile-based solvents. After polymerization in these organic solvents, an alkaline aqueous solution is added to neutralize the carboxyl group and convert it into an aqueous solution, thereby obtaining a carbon material dispersion containing the organic solvent.

[0048] Examples of the amide solvent include dimethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropanamide, and 3-butoxy-N,N-dimethylpropanamide. Examples of the urea solvent include tetramethylurea and 1,3-dimethylimidazolidinone. Examples of the nitrile solvent include acetonitrile.

[0049] It is difficult to produce the AB block copolymer used as a polymer dispersant by a normal radical polymerization method. For this reason, it is preferable to produce the AB block copolymer by a polymerization method having living properties, such as a living anionic polymerization method, a living cationic polymerization method, or a living radical polymerization method. Among them, the living radical polymerization method is particularly preferable from the viewpoints of conditions, materials, and equipment.

[0050] Examples of living radical polymerization methods include atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer polymerization (RAFT), nitroxide polymerization (NMP), organotellurium polymerization (TERP), reversible transfer catalyzed polymerization (RTCP), and reversible catalyst-mediated polymerization (RCMP). Among them, the RTCP or RCMP methods, which use an organic compound as a catalyst and an organic iodide as a polymerization initiator, are preferred. These methods use relatively safe commercially available compounds, do not use heavy metals or special compounds, and are advantageous in terms of cost and purification. Furthermore, by making the growth terminal a tertiary iodine, a precise block structure can be easily formed using general equipment.

[0051] When producing an AB block copolymer, either polymer block A or polymer block B may be polymerized first. However, if polymer block B is polymerized first, methacrylic acid may remain in the polymerization system. In this case, an excessive amount of structural units derived from methacrylic acid may be introduced into polymer block A, which is polymerized thereafter. For this reason, it is preferable to polymerize polymer block A first and then polymerize polymer block B.

[0052] When the carbon material contains SWCNT, the amount of the dispersant relative to 100 parts by mass of SWCNT must be 50 parts by mass or more and 600 parts by mass or less, more preferably 70 parts by mass or more and 500 parts by mass or less, and particularly preferably 100 parts by mass or more and 300 parts by mass or less. When the carbon material contains MWCNT, the amount of the dispersant relative to 100 parts by mass of MWCNT must be 20 parts by mass or more and 200 parts by mass or less, more preferably 25 parts by mass or more and 150 parts by mass or less, and particularly preferably 30 parts by mass or more and 100 parts by mass or less. By setting the amount of the dispersant relative to the carbon material within the above ranges, a carbon material dispersion in which the carbon material is more stably dispersed can be obtained. If the amount of the dispersant relative to the carbon material is too small, the dispersant cannot sufficiently cover the surface of the carbon material, and the dispersibility may be somewhat insufficient. On the other hand, if the amount of the dispersant relative to the carbon material is too large, the carbon material dispersion may be easily thickened and the ratio of the carbon material in the solid content may be relatively low. Furthermore, the surface resistivity of the formed coating film becomes somewhat high, and when an electrode is formed, the cycle characteristics of the electrode may deteriorate.

[0053] (binder resin) The carbon material dispersion liquid according to the present embodiment further contains a binder resin. By containing the binder resin, it is possible to form a conductive coating film that is excellent in properties such as elongation and bending, and has improved adhesion to a substrate or the like. As the binder resin, in consideration of affinity with the dispersant, it is preferable to use a cellulose derivative such as carboxymethylcellulose (including Na salt); a styrene-butadiene copolymer; and an acrylic resin such as a styrene-acrylic resin.

[0054] The content of the binder resin relative to the carbon material in the carbon material dispersion liquid is, for example, in the case of single-walled carbon nanotubes, 300 parts by mass or more and 850 parts by mass or less, preferably 350 parts by mass or more and 800 parts by mass or less, relative to 100 parts by mass of single-walled carbon nanotubes. In the case of multi-walled carbon nanotubes, it is necessary to have 700 parts by mass or more and 880 parts by mass or less, more preferably 700 parts by mass or more and 870 parts by mass or less, relative to 100 parts by mass of multi-walled carbon nanotubes. If the amount of the binder resin is too small, it may be difficult to apply the binder resin to the substrate, and a homogeneous electrode may not be obtained. If the amount of the binder resin is too large, the ratio of the active material (carbon material) may relatively decrease, and sufficient battery capacity may not be obtained when the battery is formed. Furthermore, when the carbon material dispersion liquid is used for coating applications, the content of the binder resin relative to the carbon material in the carbon material dispersion liquid must be 300 parts by mass or more and 850 parts by mass or less, and preferably 350 parts by mass or more and 800 parts by mass or less, relative to 100 parts by mass of the carbon material. Furthermore, when the carbon material dispersion liquid is used for battery applications, the content of the binder resin relative to the carbon material in the carbon material dispersion liquid must be 700 parts by mass or more and 880 parts by mass or less, and more preferably 700 parts by mass or more and 870 parts by mass or less, relative to 100 parts by mass of the carbon material.

[0055] (Additives, etc.) The carbon material dispersion liquid according to the present embodiment may further contain additives and resins. Examples of additives include water-soluble dyes, pigments, ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoamers, preservatives, antifungal agents, photopolymerization initiators, and other pigment dispersants. Examples of resins include polyolefin resins, polyhalogenated olefin resins, polyester resins, polyamide resins, polyimide resins, polyether resins, polyvinyl resins, polystyrene resins, polyvinyl alcohol resins, polymethacrylate resins, polyurethane resins, polyepoxy resins, polyphenol resins, polyurea resins, and polyethersulfone resins.

[0056] It is preferable to add an antifoaming agent as an additive to the carbon material dispersion liquid depending on the device used in the wetting and dispersing steps. By adding an antifoaming agent, foaming during the dispersion treatment can be suppressed, so that the shear force, collision force, etc. applied during the dispersion treatment can act effectively, resulting in a dispersion liquid with better dispersibility.

[0057] (Absorbance of carbon material dispersion) The absorbance of a dispersion of a carbon material containing carbon nanotubes forms a gentle curve from 300 nm to 1,000 nm in wavelength. However, this curve (absorbance curve) varies greatly depending on the dispersion state of the carbon nanotubes. For example, the absorbance on the short wavelength side shows a large value when there is a large amount of finely dispersed carbon nanotubes. On the other hand, the absorbance on the long wavelength side shows a large value when there is a large amount of carbon nanotube aggregates. Therefore, the absorbance on the short wavelength side (A L ) and the absorbance on the long wavelength side (A H ) and the absorbance ratio (A L / A H ) closely reflects the dispersion state of the carbon material in the liquid medium. That is, the more finely and uniformly the carbon nanotubes are dispersed, the larger the absorbance ratio will be, and the smaller the absorbance ratio will be if the carbon nanotubes are aggregated.

[0058] Reference wavelength W M is the wavelength on the short wavelength side, W L and the wavelength on the long wavelength side, W H Median of (W M =(W L +W H ) / 2). The wavelength region near the median is hardly affected by the dispersion state of the carbon material, and is therefore suitable as a standard for evaluating the dispersibility of the carbon material.

[0059] Short wavelength W Lis arbitrarily selected from the range of 350 nm to 550 nm, preferably from the range of 350 nm to 450 nm, more preferably from the range of 350 nm to 400 nm. The absorbance at wavelengths within the above range changes clearly, and there is little noise or specific peak change, so that it can be measured stably. If it is less than 350 nm, the absorption and scattering of light by the fine particles will have an irregular effect, and the peak will change significantly as the dispersion progresses, making it difficult to use it as an accurate indicator. On the other hand, if it is more than 550 nm, the change in absorbance will be unclear.

[0060] Long wavelength W H is arbitrarily selected from the range of 650 nm to 850 nm, preferably from the range of 700 nm to 850 nm, more preferably from the range of 700 nm to 800 nm. If the wavelength is within the above range, the absorbance of particles with a small proportion of absorbing components and a large proportion of scattering components can be confirmed. In addition, there is little noise or specific peak change, and the measurement can be performed stably. If it is more than 850 nm, noise will be mixed into the peak, making it difficult to measure an accurate value. On the other hand, if it is less than 650 nm, it is not suitable as an index.

[0061] Wavelength W L and wavelength W H The difference between the wavelengths W is preferably 100 nm or more, and more preferably 200 nm or more. L and wavelength W H By making the difference between the wavelengths W and W equal to or greater than 100 nm, the dispersibility of the carbon material can be read more accurately. L and wavelength W H If the difference is too small, it may be difficult to accurately evaluate the dispersion state of the carbon material.

[0062] The absorbance of the dispersion varies depending on the content (concentration) of the carbon material. For this reason, the absorbance of a dilute dispersion prepared by diluting a dispersion not containing a binder resin and a dispersion containing a binder resin, as necessary, is measured. As a dilution liquid for diluting the dispersion, it is preferable to use a blank liquid having the same composition as the target dispersion except that it does not contain a carbon material. By using such a blank liquid, the influence of the diffusion and re-aggregation of fine particles and the environment on the absorbance can be suppressed, and the absorbance can be measured more accurately by reducing the influence of the polymer dispersant that is sometimes used as a dispersant.

[0063] In order to measure absorbance accurately, it is usually preferable that the content of the carbon material in the sample liquid (dilute dispersion liquid) is in the range of 0.001% by mass or more and 0.01% by mass or less. If it exceeds 0.01% by mass, the amount of scattered laser light transmitted during measurement is small, which may make accurate measurement difficult. On the other hand, if it is less than 0.001% by mass, the absorbance value becomes too small, which may make accurate evaluation or comparison difficult.

[0064] The wavelength W of the dilute dispersion obtained by diluting with a diluent containing the liquid medium M The absorbance of the dilute dispersion is 1.2 or more and 2.2 or less, and preferably 1.5 or more and 2.0 or less. M If the absorbance is less than 1.2, it is difficult to judge the dispersion state, whereas if the absorbance is more than 2.2, it is difficult to measure accurately.

[0065] Wavelength W of dilute dispersion H Absorbance A H For wavelength W L Absorbance A L Ratio of (A L / A H ) is the wavelength W H and W L For example, the wavelength W L = 380 nm and wavelength W H = 780 nm L / A H If the value of " is "1.60 → 1.45", the wavelength WL = 400 nm and wavelength W H = 700 nm L / A H " value is "1.44 → 1.29", and the wavelength W L = 350 nm and wavelength W H = 800 nm L / A H The value of " is "1.78 → 1.63". Also, the wavelength W L = 380 nm and wavelength W H = 780 nm L / A H If the value of " is 1.65 → 1.50", the wavelength W L = 400 nm and wavelength W H = 700 nm L / A H " value is "1.48 → 1.33", and the wavelength W L = 350 nm and wavelength W H = 800 nm L / A H " The value is "1.85→1.70".

[0066] Wavelength W L The absorbance of the dilute dispersion at wavelength W is a physical property that serves as an index of the dispersion state of the carbon material. H The absorbance of the dilute dispersion at wavelength W is a physical property that serves as an index of the aggregation state of the carbon material. L and W H The wavelength W is the median M is used as a reference, and this wavelength W M The absorbance of the diluted dispersion is 1.2 to 2.2 at wavelength W H Absorbance A H For wavelength W L Absorbance A L Ratio of (A L / A H ) value, the dispersion state of the carbon material in the dispersion liquid can be accurately evaluated.

[0067] The dilute dispersion has a wavelength of W L is 380 nm, wavelength W His 780 nm, and the wavelength W M is 580 nm, and the wavelength W M is 1.8±0.02, the absorbance A H Absorbance A L Ratio of (A 380 / A 780 The absorbance ratio (A) must be 1.45 or more, and is more preferably 1.50 or more in order to make the short side of the aggregate less than 100 μm. In order to disperse the carbon nanotubes more uniformly in the liquid medium after the dispersion treatment, it is particularly preferably 1.55 or more. 380 / A 780 By setting the value of (a) within the above range, even if the types or amounts of the carbon material, dispersant, and binder resin vary, it is possible to provide a dispersion that does not substantially contain coarse aggregates and has better viscosity stability. Absorbance ratio (A 380 / A 780 The value of (a) can be achieved by adjusting the type or amount of the carbon material or dispersant, or by adjusting the wetting method or dispersion method of the dispersion.

[0068] Absorbance ratio (A 380 / A 780 If the absorbance ratio (A) is less than 1.45, the carbon nanotubes are not finely and uniformly dispersed, so the viscosity stability of the dispersion is low and many coarse aggregates are included. 380 / A 780 The dispersion according to this embodiment, in which the viscosity coefficient is 1.45 or more, contains carbon material including carbon nanotubes in a finely and uniformly dispersed state, has good viscosity stability, is substantially free of coarse aggregates, and even if fine aggregates are contained, the amount is extremely small.

[0069] The absorbance ratio of the dispersion is preferably high, regardless of whether or not a binder resin is present. Even if a binder resin is added to a poorly dispersed dispersion that does not contain a binder resin, the absorbance ratio is hardly improved, and sufficient performance may not be exhibited.

[0070] (Physical properties of carbon material dispersion) The dispersion according to the present embodiment has excellent viscosity stability (storage stability) and does not easily change viscosity even after a long period of time. Specifically, the rate of change in viscosity (mPa·s) of the binder resin-free dispersion at 25°C after 10 days at room temperature (25°C) is usually 15% or less, preferably 10% or less, and more preferably 5% or less, based on the viscosity (mPa·s) of the binder resin-free dispersion at 25°C immediately after preparation (dispersion).

[0071] If aggregates with a short side of 100 μm or more are present in a dispersion liquid that does not contain a binder resin, when the dispersion liquid is applied to various applications, the inherent performance of carbon nanotubes, such as electrical conductivity or thermal conductivity, is difficult to exhibit, and the growth or precipitation of the aggregates occurs, which tends to reduce viscosity stability and storage stability. For example, when a dispersion liquid containing aggregates with a short side of 100 μm or more is used as a coating material, uniform coating tends to be difficult. In contrast, the dispersion liquid according to the present embodiment does not substantially contain coarse aggregates formed by carbon materials including carbon nanotubes. Specifically, even when a dispersion liquid without a binder resin immediately after preparation (dispersion) and a dispersion liquid without a binder resin after 10 days have passed under room temperature (25° C.) conditions are observed five times at a magnification of 200 times using an optical microscope, not even one aggregate with a short side of 100 μm or more is usually observed. Preferably, the number (average value) of aggregates with a short side of 20 μm or more is 10 or more per observation. More preferably, the number (average value) of agglomerates with short sides of 20 μm or more is 1 or more and less than 10 per observation, and particularly preferably, not a single agglomerate with short sides of 20 μm or more is found even after five observations.

[0072] (Method of producing carbon material dispersion) The carbon material dispersion liquid can be produced by prewetting the carbon material including carbon nanotubes in a liquid medium using a dispersant according to a conventionally known method, and then dispersing the carbon material. For example, a wetting method and a dispersion method using a magnetic stirrer stirring, a dissolver stirring, a three-roll kneading, an ultrasonic dispersion, a bead mill dispersion, an emulsifier, a homogenizer, etc. can be used. From the viewpoint of process simplicity, it is preferable to stir and wet the material using a magnetic stirrer, a dissolver, and a homogenizer, and it is preferable to disperse the material in combination with a high-pressure homogenizer. For example, it is preferable to disperse the material using a bead mill using small-diameter beads. In addition, the wetting method and the dispersion method may be combined in consideration of damage to carbon materials such as carbon nanotubes.

[0073] When mixing multiple dispersions or adding and mixing a binder resin, a dispersing machine may be used in addition to a magnetic stirrer. Mixing using a dispersing machine is preferable because it can prevent shock aggregation and the like, and therefore a dispersion with a better dispersion state can be obtained.

[0074] When dispersing the carbon material containing carbon nanotubes, a binder resin may be added to the liquid medium, and if the dispersion state of the carbon nanotubes in the obtained dispersion liquid is good, the electrical conductivity will not decrease. Adding a binder resin during dispersion is preferable because it can prevent shock aggregation and the like.

[0075] (Paint film) A conductive coating film (film) can be formed by applying and drying the carbon material dispersion liquid according to this embodiment. The concentration of the carbon material in the coating film to be formed is, for example, preferably 0.01% by mass or more and 50% by mass or less, more preferably 0.1% by mass or more and 30% by mass or less, and particularly preferably 0.5% by mass or more and 20% by mass or less. The thickness (film thickness) of the coating film can be, for example, 0.8 μm or more and 30 μm or less. The thicker the film thickness and the higher the concentration of the carbon material, the lower the surface resistivity of the coating film. It was confirmed that the surface resistivity of the coating film hardly changes if the film thickness is within the range of 1±0.2 μm and the concentration of the carbon material is within the range of 10±0.5% by mass.

[0076] The surface resistivity of a 1 μm-thick dry film (coating) containing 10 mass % carbon material formed by applying and drying the carbon material dispersion liquid according to this embodiment is 1.0×10 3 It is necessary that the resistance is Ω / sq or less, and preferably 9.0×10 2 The carbon content in the dried film (coating) can be calculated by subtracting the mass (solid content) of the dispersant and binder resin used from the mass of the dried film formed by heating the coating film formed by applying the dispersion and evaporating the aqueous liquid medium. The surface resistivity of the dry film can be achieved by adjusting the type or amount of the carbon material or dispersant, or by adjusting the wetting method or dispersion method of the dispersion.

[0077] <Use of carbon material dispersion> In the carbon material dispersion according to the present embodiment, the carbon material including the carbon nanotubes is well dispersed without substantially generating coarse aggregates, and has excellent viscosity stability. In addition, since the carbon material dispersion according to the present embodiment is an aqueous dispersion, it is an environmentally friendly material and is useful as a material for producing paints, inks, coating agents, and materials for resin molded products. In addition to being expected to be used as a conductive material or a thermally conductive material, it is also expected to be applied to antistatic materials. Furthermore, it is useful as a material for forming a film constituting a battery material such as an electrode material constituting a battery such as a lithium ion battery and a fuel cell, or a film constituting a capacitor material, and a film constituting various machine parts.

[0078] The water-based paint or ink can be prepared by adding various components such as a solvent, a resin, and an additive to a carbon material dispersion. Alternatively, the carbon material dispersion may be added to a commercially available paint or ink.

[0079] A resin molded product can be produced, for example, by adding a carbon material dispersion to a plastic material in a molten state and then removing the water. Alternatively, a resin molded product in which a carbon material is dispersed can also be produced by adding a carbon material dispersion to a plastic material in a fine powder state and then removing the water or precipitating the carbon material. EXAMPLES

[0080] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0081] <Preparing materials> The following carbon material, dispersant, and binder resin were prepared.

[0082] (Carbon materials) [Single-walled carbon nanotubes (SWCNT)] ·SWCNT-1: Product name "Tuball", manufactured by OCSiAl, average length 2~20μm SWCNT-2: Product name "SG101", manufactured by Zeon Corporation, average length 100-600μm

[0083] [Multi-walled carbon nanotubes (MWCNT)] ·MWCNT-1: Product name "400T", manufactured by KUMHO, average length 90~100μm ·MWCNT-2: Product name "s5", manufactured by SUSN, average length 40~80μm MWCNT-3: Product name "Multi-walled carbon nanotube flakes", manufactured by Hamamatsu Carbonix, average length 500-1500μm ·MWCNT-4: Product name "s4", manufactured by SUSN, average length 5~20μm

[0084] [Carbon Black (CB)] CB-1: Product name "Li435", manufactured by Denka

[0085] (Dispersant) Dispersant d: Product name "Floren GW-1500", styrene-maleic acid modified polymer, manufactured by Kyoeisha Chemical Co., Ltd., solid content 100%, acid value 55 mgKOH / g, amine value 0 mgKOH / g, weight average molecular weight 5,000 Dispersant e: Product name "Disparlon AQ-380", acrylic polymer, manufactured by Kusumoto Chemicals, solid content 30%, acid value 15 mg KOH / g, amine value 11 mg KOH / g

[0086] (binder resin) Binder resin A: Product name "YL-1098", styrene acrylic resin, manufactured by Seiko PMC Corporation Binder resin B: Dispersant c Binder resin C: A mixture of dispersant C and styrene-butadiene copolymer latex (product name "Nalstar SR-112", manufactured by Nippon A&L Co., Ltd.) (dispersant C: styrene-butadiene copolymer latex = 4:1)

[0087] <Production of Dispersants (1)> (Dispersant a) 233.3 parts of N-methylpyrrolidone (NMP) were placed in a reaction vessel and stirred, and the temperature was raised to 70°C. 60 parts of acrylonitrile (AN), 40 parts of acrylic acid (AA), and 3.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (trade name "V-65", Fujifilm Wako Pure Chemical Industries, Ltd.) (V-65) were placed in a beaker, and V-65 was completely dissolved to prepare a monomer solution. The prepared monomer solution was placed in a dropping funnel, and when the temperature in the reaction vessel reached 70°C, 1 / 3 of the total amount was added, and the remaining liquid was dropped over 1.5 hours. After the dropwise addition, 2.5 hours had passed, and 1.0 part of V-65 was added. After maintaining at 70°C for 1 hour, the temperature was raised to 80°C and maintained for 2 hours to form a polymer. After cooling, the solid content was measured using a moisture meter, and it was confirmed that almost all of the monomer had been consumed. The number average molecular weight (Mn) of the polymer, calculated as polymethyl methacrylate, measured by gel permeation chromatography (GPC) using a solution of lithium bromide in N,N-dimethylformamide (lithium bromide concentration: 10 mmol / L) as the developing solvent was 25,300, and the molecular weight distribution (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) was 2.24.

[0088] 24.4 parts of sodium hydroxide (NaOH) (110 mol% relative to AA) and 96.8 parts of ion-exchanged water were placed in a beaker, and NaOH was completely dissolved to prepare an aqueous NaOH solution. After the temperature inside the reaction vessel reached 60°C or lower, the aqueous NaOH solution was added to neutralize the carboxyl groups, and a solution of polymer dispersant (dispersant a) was obtained. The solid content of the resulting solution of dispersant a was 22.1%.

[0089] (Dispersant b) 255.4 parts of 3-methoxy-N,N-dimethylpropanamide (MDMPA), 1.0 part of iodine, 3.7 parts of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (trade name "V-70", Fujifilm Wako Pure Chemical Industries, Ltd.) (V-70), 0.2 parts of diphenylmethane (DPM), 106.1 parts of AN, and 26.5 parts of methacrylic acid (MAA) were placed in a reaction vessel. The mixture was stirred while flowing nitrogen, heated to 40°C, and polymerized for 4 hours to form an A chain. The solid content of the reaction solution was 34.8%, and the polymerization conversion calculated from the solid content was about 100%. The Mn of the formed A chain was 14,800, the PDI was 1.41, and the peak top molecular weight (PT) was 20,700.

[0090] After adding 3.1 parts of V-70, a monomer solution containing 30.0 parts of AN, 31.8 parts of MAA, and 216.9 parts of MDMPA was further added. Then, polymerization was carried out at 40°C for 4 hours to form a B chain, and an AB block copolymer was obtained. The solid content of the reaction solution was 29.9%, and it was confirmed that the target product was obtained almost quantitatively. The Mn of the obtained AB block copolymer was 21,600, the PDI was 1.52, and the PT was 32,700. The molecular weight of the B chain can be calculated by subtracting the Mn of the A chain from the Mn of the AB block copolymer. That is, the Mn of the B chain was 6,800, and the PT was 12,000.

[0091] 29.8 parts of NaOH (110 mol% relative to MAA) and 105.1 parts of ion-exchanged water were placed in a beaker, and NaOH was completely dissolved to prepare an aqueous NaOH solution. The aqueous NaOH solution was poured into a reaction vessel to neutralize the carboxyl groups, and a solution of polymer dispersant (dispersant b) was obtained. The solid content of the obtained solution of dispersant b was 25.1%.

[0092] (Dispersant C) In a 1L stainless steel container equipped with a stirrer, 400g of isopropyl alcohol (IPA) and 60g of water were placed, and 10g of sodium hydroxide (purity 98%) was added while cooling the stainless steel container. After the solution was cooled to below 25°C, 20g of ground pulp was added while stirring. Then, the mixture was stirred and mixed (mercerized) at 15-25°C for 60 minutes to prepare alkali cellulose. Next, 30g of a mixed solution of monochloroacetic acid / isopropyl alcohol = 1:2 was added while cooling the stainless steel container to keep it at 15-25°C, and stirred and mixed for 15 minutes. Next, while heating the stainless steel container, the temperature of the solution was raised to 70°C over about 30 minutes. The mixture was stirred at 65-75°C for 120 minutes to perform an etherification reaction. After the reaction was completed, unreacted sodium hydroxide was neutralized with acetic acid, and the product was separated. The by-products were removed by washing with a 70% aqueous methanol solution. The product was dried and pulverized to obtain carboxymethylcellulose sodium salt (dispersant c). The viscosity of a 1% aqueous solution of the obtained sodium carboxymethylcellulose was 31 mPa·s, and the degree of etherification (DS) was 0.84.

[0093] The degree of etherification was measured with reference to the synthetic detergent JIS related substance test method described in Oil Chemistry 38(11), 962-967, 1989. Specifically, about 1 g of sodium carboxymethylcellulose salt was precisely weighed and placed in a porcelain crucible, and then heated at a temperature not exceeding 600°C (approximately 550-590°C) for 1 hour to incinerate. After cooling to room temperature, the crucible was transferred to a 500 mL beaker and 250 mL of water was added. 50 mL of 0.05 mol / L sulfuric acid aqueous solution was added and boiled for 30 minutes. After cooling to room temperature, the unreacted acid was titrated with 0.1 mol / L sodium hydroxide. Phenolphthalein was used as the indicator. The amount of 0.1 mol / L sodium hydroxide used in the titration was designated as "X" mL, and the degree of etherification (DS) was calculated by the following formula. Degree of etherification (DS) = 162X / (10000-80X)

[0094] <Measurement and evaluation methods> (Calculation of average CNT length) The CNT powder was observed under an electron microscope, and the average length was calculated for 10 randomly selected nanotubes. This procedure was carried out for five batches, and the numerical range for the average length was determined.

[0095] (Measurement of absorbance and calculation of absorbance ratio) A blank solution having the same composition as the carbon material dispersion liquid except that it does not contain a carbon material was prepared. After measuring the baseline using the prepared blank solution, the absorbance of the sample solution was measured. The absorbance of the sample solution was measured using a spectrophotometer (trade name "Hitachi Spectrophotometer U-3310 type", manufactured by Hitachi High-Tech Science Corporation) equipped with a quartz cell with an optical path length of 10 mm. Regarding dilution with the blank solution, a calibration curve was prepared by plotting the absorbance at a wavelength of 580 nm depending on the change in dilution ratio, and the dilution ratio was calculated so that the absorbance was 1.8 ± 0.02, thereby preparing a dispersion solution diluted to the desired concentration. In addition, it is also possible to adjust the carbon component concentration to the desired concentration before dispersion, or to adjust the carbon component concentration to satisfy the absorbance at the initial blending stage and then perform dispersion. In a specific sample solution preparation method, first, the dispersion solution was collected in a poly bottle (polyethylene bottle), and an appropriate amount of blank solution was added based on the dilution ratio obtained by the calibration curve. The solution was stirred for 30 seconds using a vortex mixer (Scientific Industries) and the absorbance A at a wavelength of 580 nm was measured. 580 The absorbance A of the obtained sample solution at a wavelength of 380 nm was 1.8±0.02. 380 and absorbance A at a wavelength of 780 nm 780 The absorbance ratio (A 380 / A 780 The measurement was carried out on the dispersion immediately after dispersion and on the dispersion after the binder resin was added.

[0096] (Evaluation of Dispersion) [Measurement of viscosity and evaluation of viscosity stability] Using an E-type viscometer equipped with a rotor of 1°34' x R24, the viscosity of the dispersion not containing the binder resin immediately after dispersion and after 10 days (after leaving it at room temperature for 10 days) was measured at a temperature of 25°C and a rotor rotation speed of 100 rpm. For dispersions with a viscosity of less than 25 mPa·s, the viscosity was measured using a product called "VISCOMETER TVE-25L" (manufactured by Toki Sangyo Co., Ltd.). For dispersions with a viscosity of 25 mPa·s or more, the viscosity was measured using a product called "VISCOMETER TVE-25H" (manufactured by Toki Sangyo Co., Ltd.). The viscosity stability of the dispersions was evaluated according to the following evaluation criteria. ⊚: The rate of change in viscosity after 10 days based on the viscosity immediately after dispersion is less than 5%. ◯: The rate of change in viscosity after 10 days based on the viscosity immediately after dispersion is 5% or more and less than 10%. △: The rate of change in viscosity after 10 days based on the viscosity immediately after dispersion is 10% or more and less than 15%. ×: The rate of change in viscosity after 10 days based on the viscosity immediately after dispersion is 15% or more.

[0097] [Aggregate observation] A dispersion liquid not containing a binder resin was collected in a polyethylene bottle (polyethylene bottle), and a blank liquid was added to dilute the dispersion so that the concentration of the carbon material was 0.1% by mass. A diluted solution was obtained by stirring for 30 seconds using a vortex mixer (manufactured by Scientific Industries). 30 μL of the obtained diluted solution was dropped onto a slide glass, a cover glass was placed on it, and the presence or absence of aggregates was observed using an optical microscope (200 times). For the dispersion liquid not containing a binder resin immediately after dispersion and the dispersion liquid not containing a binder resin 10 days later (after leaving it at room temperature for 10 days), samples were prepared by dropping five times onto the slide glass, and the presence or absence of aggregates was evaluated according to the evaluation criteria shown below. ⊚: Not a single aggregate with a short side of 20 μm or more was observed during five observations. ◯: The number (average value) of aggregates with short sides of 20 μm or more was 1 or more and less than 10 per observation, and not a single aggregate with short sides of 100 μm or more was observed in any of the five observations. △: The number (average value) of aggregates with short sides of 20 μm or more was 10 or more per observation, and not a single aggregate with short sides of 100 μm or more was observed in any of the five observations. ×: One or more aggregates with a short side of 100 μm or more were observed during five observations.

[0098] (Evaluation of coating film) [Surface resistivity measurement] Surface resistivity is 10 5 When the surface resistivity of the coating film exceeded Ω / sq, a high-resistance resistivity meter (trade name "Hi-resta-UP MCP-HT450", manufactured by Mitsubishi Chemical Analytech Co., Ltd.) was used to measure the surface resistivity of the coating film at five points with an applied voltage of 10 V, and the average value was calculated. 5 When the value was Ω / sq or less, a low resistance resistivity meter (product name "Loresta-GP MCP-T610", manufactured by Mitsubishi Chemical Analytech Co., Ltd.) was used, and the average surface resistivity of the coating film was calculated by measuring five points with an applied voltage of 10 V.

[0099] [Observation of coating material] A dispersion containing a binder resin was applied to a PET film to form a dried film measuring 10 cm square. The film was visually observed and evaluated for cracks, peeling, and unevenness according to the following evaluation criteria. ⊚: No cracks, peeling, or unevenness was observed in any place. ◯: Any of cracks, peeling, and unevenness was present in an area of ​​less than 5% of the entire dry film. Δ: Any of cracks, peeling, and unevenness was present in an area of ​​5% or more and less than 30% of the entire dry coating area. x: Any of cracks, peeling, and unevenness was present in a proportion of 30% or more of the entire area of ​​the dried film.

[0100] <Preparation and Evaluation of Dispersion Liquid (1)> (Dispersion 1~22) The type and amount of dispersant and water shown in Table 1 were placed in a 200 mL plastic bottle (polyethylene bottle). After stirring with a magnetic stirrer until uniform, the type and amount of carbon material shown in Table 1 was added and further stirred. Next, a high-pressure homogenizer (manufactured by Joko Co., Ltd.) was used to perform high-pressure treatment at a treatment pressure of about 10 MPa. After that, a high-pressure homogenizer (manufactured by Sugino Machine Co., Ltd.) was used to perform high-pressure dispersion treatment at a treatment pressure of about 100 MPa to obtain a dispersion. The number of passes of the dispersion (number of treatments of high-pressure dispersion treatment) is shown in Table 1. Note that the number of passes was 0, so the high-pressure dispersion treatment was not performed. In addition, the evaluation results of the viscosity stability of the obtained dispersion and the results of the observation of aggregates are shown in Table 3.

[0101] (Mixtures 1 and 2) The first and second dispersions shown in Table 2 were mixed so that the carbon material 1 and the carbon material 2 were in the mass ratio shown in Table 2, and then mixed using a magnetic stirrer to obtain a mixture. The evaluation results of the viscosity stability of the obtained mixture and the results of the observation of aggregates are shown in Table 3.

[0102] [Table 1]

[0103] [Table 2]

[0104] [Table 3]

[0105] Example 1 ~5, Example 7 ~15, Reference example 1~ 6 , and Comparative Examples 1 to 10) The types of dispersions and binder resins shown in Table 5 were mixed in a ratio such that the concentration of the carbon material in the coating film (solid content) formed would be the value (%) shown in Table 5, and then mixed using a magnetic stirrer to obtain a carbon material dispersion. Table 4 shows the absorbance ratio for some of the carbon material dispersions. Table 4 also shows the number of passes for the dispersions used. The obtained carbon material dispersions were each coated on a PET film (product name "Lumirror", manufactured by Toray Industries, Inc.) with a thickness of 100 μm using a bar coater, and then dried in an electric oven at 90° C. for 30 minutes to remove volatile components, forming a coating film with a thickness shown in Table 5. Table 5 shows the surface resistivity of the formed coating film. In Comparative Example 6, cracks and peeling occurred over a wide area of ​​the coating during drying, and the smooth coating surface required for measuring the surface resistivity could not be secured, so evaluation was abandoned.

[0106] [Table 4]

[0107] [Table 5]

[0108] (Application Example 1-1: Battery Materials (Anode)) The following materials were used to manufacture the negative electrode of the lithium-ion battery: [Negative electrode activator] Graphene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Silicon monoxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) [Binder resin] 10% polyacrylic acid aqueous solution (product name "CLPA-C07", Fujifilm Wako Pure Chemical Industries, Ltd.) Carboxymethylcellulose (product name "CMC Daicel 2200", manufactured by Daicel Miraize Co., Ltd.) Styrene butadiene copolymer latex (product name "Nalstar SR-112", manufactured by Nippon A&L Co., Ltd.)

[0109] 15 parts of silicon monoxide, 85 parts of graphene, 3 parts of dispersion 2, 30 parts of 10% polyacrylic acid aqueous solution, 1.6 parts of carboxymethyl cellulose, and 0.4 parts of styrene-butadiene copolymer latex were mixed using a planetary mixer to obtain a negative electrode material. The weight of the negative electrode material after drying was 15 mg / cm. 2 The negative electrode material was applied to a copper foil with a thickness of 20 μm using an applicator so that the negative electrode material was applied to a copper foil with a thickness of 20 μm. The negative electrode was dried in an oven set at 120°C for 30 minutes, and then rolled with a roll press to obtain a negative electrode. The volume resistivity of the obtained negative electrode was 0.16 Ω cm, and the capacity retention rate was 95%.

[0110] (Application Example 1-2: Battery Materials (Anode)) A negative electrode was manufactured in the same manner as in Application Example 1-1 described above, except that Dispersion 15 was used instead of Dispersion 2. The volume resistivity of the manufactured negative electrode was 0.31 Ω cm, and the capacity retention rate was 93%. From the above, it was found that a negative electrode with a smaller volume resistivity value can be manufactured by using a dispersion with a good dispersion evaluation.

[0111] (Application Example 2-1: Antistatic coating agent) 100 g of dispersion 2, 100 g of polymer binder (product name "NeoPac R-9699", manufactured by Kusumoto Chemicals, acrylic urethane resin, solid content 40%), and 800 g of pure water were placed in a plastic cup and stirred with a dissolver to obtain an antistatic coating agent. The obtained antistatic coating agent was applied to the surface of a 38 μm-thick polyethylene terephthalate film (manufactured by Toray Industries, Inc.) using a bar coater so that the coating film after drying would be 0.5 μm thick. The film was dried in an oven set at 80° C. for 10 minutes to obtain an antistatic coating film. The surface resistivity of the obtained film was 9.6×10 5 Ω / cm 2 It was.

[0112] (Application Example 2-2: Antistatic coating agent) An antistatic coating film was produced in the same manner as in Application Example 3-1, except that Dispersion 15 was used instead of Dispersion 2. The surface resistivity of the produced film was 7.4×107 Ω / cm 2 From the above, it was found that by using a mixed solution with a good dispersion evaluation, an antistatic coating film with a smaller surface resistivity value can be produced. [Industrial Applicability]

[0113] The carbon material dispersion of the present invention is useful as a constituent material for paints, inks, resin molded products, and the like that exhibit properties such as high electrical conductivity or high thermal conductivity, and is also suitable for various applications such as battery materials, electronic component trays, IC chip covers, electromagnetic wave shields, automotive parts, and robot parts.

Claims

1. The carbon material contains at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes, an aqueous medium, a dispersant, and a binder resin; The dispersant is at least one selected from the group consisting of surfactants and polymer dispersants, the polymer dispersant is a styrene-maleic acid modified polymer or a polymer having a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid, the binder resin is at least one selected from the group consisting of cellulose derivatives, styrene-butadiene copolymers, and acrylic resins (excluding those having the structural unit (1)); A carbon material dispersion satisfying the following requirements (1), (2), and (3): (1) When the carbon material contains the single-walled carbon nanotubes, the amount of the dispersant is 50 parts by mass or more and 600 parts by mass or less relative to 100 parts by mass of the single-walled carbon nanotubes, and the amount of the binder resin is 300 parts by mass or more and 850 parts by mass or less relative to 100 parts by mass of the single-walled carbon nanotubes, When the carbon material contains the multi-walled carbon nanotubes, the amount of the dispersant per 100 parts by mass of the multi-walled carbon nanotubes is 20 parts by mass or more and 200 parts by mass or less, and the amount of the binder resin per 100 parts by mass of the multi-walled carbon nanotubes is 700 parts by mass or more and 880 parts by mass or less. (2) The surface resistivity of a dry film having a thickness of 1 μm and containing 10% by mass of the carbon material is 1.0×10 3 Ω / sq or less. (3) The absorbance A at a wavelength of 780 nm of a dilute dispersion obtained by diluting the carbon material dispersion with a blank liquid having the same composition as the carbon material dispersion except that the carbon material is not contained, is 1.8±0.

02. H Absorbance A at a wavelength of 380 nm L The ratio (A L / A H ) is 1.45 or more.

2. The carbon material contains at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes, an aqueous medium, a dispersant, and a binder resin; The dispersant is a cellulose derivative, The binder resin is at least one selected from the group consisting of a styrene-butadiene copolymer and an acrylic resin, A carbon material dispersion satisfying the following requirements (1), (2), and (3): (1) When the carbon material contains the single-walled carbon nanotubes, the amount of the dispersant is 50 parts by mass or more and 600 parts by mass or less relative to 100 parts by mass of the single-walled carbon nanotubes, and the amount of the binder resin is 300 parts by mass or more and 850 parts by mass or less relative to 100 parts by mass of the single-walled carbon nanotubes, When the carbon material contains the multi-walled carbon nanotubes, the amount of the dispersant per 100 parts by mass of the multi-walled carbon nanotubes is 20 parts by mass or more and 200 parts by mass or less, and the amount of the binder resin per 100 parts by mass of the multi-walled carbon nanotubes is 700 parts by mass or more and 880 parts by mass or less. (2) The surface resistivity of a dry film having a thickness of 1 μm and containing 10% by mass of the carbon material is 1.0×10 3 Ω / sq or less. (3) The absorbance A at a wavelength of 780 nm of a dilute dispersion obtained by diluting the carbon material dispersion with a blank liquid having the same composition as the carbon material dispersion except that the carbon material is not contained, is 1.8±0.

02. H Absorbance A at a wavelength of 380 nm L The ratio (A L / A H ) is 1.45 or more.

3. The average length of the single-walled carbon nanotubes is 5 μm or more and 600 μm or less, 2. The carbon material dispersion according to claim 1, wherein the multi-walled carbon nanotubes have an average length of 30 μm or more and 5,000 μm or less.

4. The carbon material dispersion according to claim 1 , wherein a concentration of the carbon material in the carbon material dispersion is 20% by mass or less.

5. Use of the carbon material dispersion according to any one of claims 1 to 4 for producing any one of products including paints, inks, coating agents, resin molding materials, conductive materials, thermally conductive materials, and antistatic materials.

6. Use of the carbon material dispersion according to any one of claims 1 to 4 for producing any one of a battery material and a mechanical part, the product having a coating formed from the carbon material dispersion.

Citation Information

Patent Citations

  • Aqueous dispersion of carbon nanotube, electroconductive composite, and method for producing the same

    JP2010254546A

  • Catalyst for carbon nanotube synthesis

    JP2015123410A

  • Coating composition

    JP2019189857A

  • Carbon nanotube water-based dispersion

    JP2019212496A

  • Single layer carbon nanotube dispersion, single layer carbon nanotube coating material and Anti-static sheet

    JP2021195546A